Pengolahan Limbah Cair Rumah Tangga Dengan Filtrasi Downflow - Saputra, Elpan; Akbar, Fajar; Chairani, Miftah; Adiningsih, Ridhayani (Jurnal Kesehatan Lingkungan Mapaccing, 2023)
Domestic liquid waste is one of the leftover materials from daily human activities that are produced all the time. The residual material is in the form of water that has been used from households including waste water from bathrooms, toilets, washing areas or cooking areas. If liquid waste contains hazardous materials and substances mixed directly with the environment, it will have an impact on decreasing environmental quality. One of the wastewater treatment systems that can be used is wastewater filtering using various types of materials, such as water hyacinth, used hoses, palm fiber and gravel. The system is considered quite effective because the inorganic materials used on average have the ability to reduce the levels of contaminants in wastewater, both through filtration and absorption processes. This type of experimental research was carried out by downflow filtration, using water hyacinth, used hose, palm fiber, and gravel as the media. The results of the research carried out by the BOD parameter before being examined were 405 mg/l this exceeded the quality standard, after processing for 24 hour contact time, 25 hour contact time, 26 hour contact time it was still above the quality standard. do the COD parameter before carrying out the examination, which is 1049.1 mg/l this exceeds the quality standard, after processing for 24 hour contact time, 25 hour contact time, 26 hour contact time it is still above the quality standard. From the results of the initial pH measurement, a pH value of 5.9 was obtained which indicated that it still did not meet the established quality standards. Conclusion from the research: Parameters of wastewater after processing still exceed the quality standard